PENGARUH FREKUENSI SIKLON TROPIS TERHADAP CURAH HUJAN DI TIMOR-LESTE - Flaviana Pinto, Fernandes; Sukarasa, I Ketut; Hendrawan, I Gede (BULETIN FISIKA; Vol 16 No 1 (2015): BULETIN FISIKA, 2015)
This study aims to determine the impact of tropical cyclone frequency to the rainfall in Timor-Leste using monthly data for 30 years. The rainfall data obtained from tropical rainfall Measuring Mission (TRMM) satellite and Global Precipitation Climatology Centre (GPCC). Daily rainfall In Situ data obtained from Direcção Nacional de Meteorologia e Geofisica (DNMG). Japan Aerospace Exploration Agency (JAXA) and Bureau of Meteorology Australia (BOM) provided for tropical cyclone data. The impact of tropical cyclone to the rainfall can be observed from the seasonal pattern of DJF, MAM, JJA and SON. The highest and the lowest correlation seasonal pattern of MAM and DJF are about r = 0.99 and r = -0.97, respectively. Correlation in the seasonal pattern of JJA and SON are about r = 0.0, it because no cyclone in this season. If we observed the daily condition between tropical cyclone frequency to rainfall, the highest correlation occurred in March 2004 and April 2011 with the resulting correlation are about r = 0.73 and r = 0.79, respectively. This is an overall correlation a week before, after and during cyclone. For along 30 years, we found the correlation in 2000 and 2006 is about r = 0.41. So that, the value of correlation coefficient obtained from 1983 to 2012 is about r = 0.19, there is not a significant impact to the rainfall when tropical cyclone doesn’t occur in Timor-Leste. Keywords: Tropical Cyclone Frequency, Rainfall, Anomaly, Correlation